1983
DOI: 10.1088/0022-3719/16/32/015
|View full text |Cite
|
Sign up to set email alerts
|

Properties of microcrystalline silicon. IV. Electrical conductivity, electron spin resonance and the effect of gas adsorption

Abstract: For pt.III see ibid., vol.16, p.2005 (1983). Measured values of the electrical conductivity, sigma , and electron spin density (g=2.0057) of microcrystalline silicon can be essentially determined by the extent of the contamination of the samples by oxygen unless special precautions are taken as regards the sample preparation and/or handling. For samples deposited at a floating potential, two kinds of oxygen incorporation are identified: irreversible formation of Si-O bonds on the grain boundaries (and on the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
72
1

Year Published

1986
1986
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(78 citation statements)
references
References 39 publications
5
72
1
Order By: Relevance
“…The conductivity decreases again when the sample is put back into air. This cycle can be repeated many times without any sign of fatigue (compare [13]). …”
Section: Conductivitymentioning
confidence: 99%
See 1 more Smart Citation
“…The conductivity decreases again when the sample is put back into air. This cycle can be repeated many times without any sign of fatigue (compare [13]). …”
Section: Conductivitymentioning
confidence: 99%
“…A very careful and detailed investigation on mc-Si:H by Vep$ rek et al [13] reports, for material prepared by the chemical transport deposition process, that atmospheric gas adsorption and/or oxidation affect surface states, electronic transport and electron spin density. It will be important to investigate and identify these effects in state-of-the-art material prepared by PECVD and HWCVD.…”
Section: Introductionmentioning
confidence: 99%
“…Matsuda et al 17 and Veprek et al 18 have already shown that a variation of the deposition temperature allows one to change from a ͗111͘ to a ͗220͘ preferential growth direction. It is commonly assumed that those planes being etched away the fastest are also those growing the fastest.…”
Section: B Crystallographic Texturementioning
confidence: 99%
“…These improvements cannot be attributed to an improvement in ZnO conductivity alone, most probably to a combination of gain in conductivity in the ZnO back contact layer, as well as to an improvement in the Si material quality. Indeed, during the pH2, all the cell sub-layers are exposed to an annealing (under vacuum at 200°C), which is thought to be beneficial to the Si material mainly [14]. Such V oc increase could however not be reproduced by applying only the annealing step (only + 10mV increase).…”
Section: Hydrogen Plasma Post-treatment On Front and Back Electrodesmentioning
confidence: 99%